Predictors of response to ambulatory pharmacist‐led diabetes care. Issue 4 (28th January 2021) - Palka, Samuel J.; Koeller, Jim M.; Davidson, DeWayne; Zeidan, Amina R.; Reveles, Kelly R.
Abstract: Purpose: Ambulatory care pharmacists have been shown to significantly improve health outcomes of patients with type 2 diabetes mellitus (T2DM); however, it is unclear which patients are most likely to benefit from these services. The primary objective of this study was to describe clinical response to pharmacist‐led diabetes care and identify baseline and interventional variables that are independently predictive of clinical response. Methods: This was a retrospective cohort study of adult patients with T2DM referred for ambulatory care pharmacist diabetes management at one of two health systems in San Antonio, Texas from January 1, 2015 to December 31, 2018. Data were collected at baseline and during 6 months of follow‐up. Clinical response was defined as hemoglobin A1C (A1C) reduction from baseline ≥1% or meeting the documented A1C goal. Predictors of clinical response were identified using multivariable logistic regression, including 25 patient and clinical intervention covariates. Results: A total of 180 patients were included. Patients were predominantly female (63%) and obese (58%) with a T2DM duration ≥10 years (67%). The median (interquartile range) change in A1C from baseline for responders and non‐responders was −2.2% (−3.7 to 1.3) and 0.4% (−0.4 to 1.05) ( P  < .001), respectively. Significant predictors of response included baseline A1C (odds ratio [OR] 1.41; 95% confidence interval [CI] 1.08‐1.85), number of completed visits with the pharmacist (OR 1.65; 95% CI 1.03‐2.64), and medication frequency reduction (OR 10.7; 95% CI 1.04‐109.9). Number of primary care provider visits was a negative predictor of response (OR 0.69; 95% CI 0.49‐0.96). Conclusion: Pharmacist‐led diabetes management was associated with reduced A1C levels in patients with T2DM. Higher patient baseline A1C, more visits with the pharmacist, and medication frequency reduction were predictive of clinical response and should be considered in future patient referral and management protocols.